Terahertz Quasi-Time Domain Spectroscopy using a 808nm multimode diode laser - Ivan Cedrick Malaluan Verona; Alexander De los Reyes; Hannah Bardolaza; Elmer Estacio (Diponegoro University Semarang Indonesia, 2023)
We report on a terahertz quasi-time domain spectroscopy (QTDS) system based on a low-cost continuous wave multimode diode laser. Commercially available low-temperature grown gallium arsenide (LT-GaAs) based photoconductive antennas (PCAs) with spiral and dipole configurations were used as emitter and detector, respectively. Terahertz pulses spaced at approximately 55 ps with a bandwidth of 400 GHz were obtained. Parametric measurements of the terahertz peak-to-peak intensity were performed by varying the injection current and temperature while maintaining incident laser power. The highest peak-to-peak intensity was obtained at 170mA injection current and 20° C temperature settings. The change in the THz peak-to-peak intensity is attributed to the mode hopping characteristics of the device which in turn, is dependent on injection current and temperature.